2011
DOI: 10.1016/j.bbcan.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Connexins: sensors and regulators of cell cycling

Abstract: It is nowadays well established that gap junctions are critical gatekeepers of cell proliferation, by controlling the intercellular exchange of essential growth regulators. In recent years, however, it has become clear that the picture is not as simple as originally anticipated, as structural precursors of gap junctions can affect cell cycling by performing actions not related to gap junctional intercellular communication. Indeed, connexin hemichannels also foresee a pathway for cell growth communication, albe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 284 publications
(350 reference statements)
1
69
0
4
Order By: Relevance
“…It is well established that gap junctions contribute to cell homeostasis by allowing the intercellular exchange of essential growth regulators, including ions, nucleotides, sugars, small peptides, RNAs (Kardamia et al, 2007;Vinken et al, 2011), and microRNAs (Lim et al, 2011). Cx26 expression is virtually absent in the normal adult airway epithelium (Chanson, Koval, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that gap junctions contribute to cell homeostasis by allowing the intercellular exchange of essential growth regulators, including ions, nucleotides, sugars, small peptides, RNAs (Kardamia et al, 2007;Vinken et al, 2011), and microRNAs (Lim et al, 2011). Cx26 expression is virtually absent in the normal adult airway epithelium (Chanson, Koval, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cx-mediated regulation of cell proliferation can occur by channel-dependent and channel-independent mechanisms (4,25). Previously published data indicated that channel functionality and the C-terminal domain are both necessary for growth suppression by Cx37 (7,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The channels are bicellular structures formed by the members of a family of about 20 related but distinct Cxs. 4,5 Six Cx monomers assemble to form a hemi-gap junction channel or connexon, which, in turn, forms a complete gap junction channel by docking with connexon from an adjacent cell. 2,3 The phosphorylation of connexin43 (Cx43) in its life cycle has been implicated in the regulation of a broad variety of Cx processes, such as the trafficking, assembly/disassembly, degradation, as well as the gating of gap junction channels.…”
Section: Introductionmentioning
confidence: 99%